2017
DOI: 10.1002/slct.201700084
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrocatalysis of Diiron Monothiolate Complexes: Small Molecule Mimics of the [FeFe] Hydrogenase Enzyme

Abstract: Reaction of the precursor complexes [Fe2(μ‐SCH2Ph)2(CO)6] 1 and [Fe2(μ‐SEt)2(CO)6] A with the phosphine ligand (L=P(PhOMe‐p)3) yielded the mono‐substituted complexes [Fe2(μ‐SCH2Ph)2(CO)5(P(PhOMe‐p)3)] 2 and [Fe2(μ‐SEt)2(CO)5(P(PhOMe‐p)3)] 3. All the complexes were characterized by various spectroscopic techniques. X‐ray crystal structure has been reported for complex 3. The reduction potentials of the phosphine substituted complexes 2 and 3 appeared at more negative potentials in comparison to the precursor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Diiron bond length for the phosphine substituted complexes 1 (2.524 Å) and 2 (2.516 Å) were slightly longer than the all‐carbonyl complex A (2.510 Å); and the values were close to the Fe−Fe bond length found in the [2Fe‐2S] unit of the iron H 2 ase enzyme (2.6 Å) [44] . The Fe−P bond distances in 1 and 2 were 2.308 Å and 2.269 Å, respectively [45–48] . For complex A , the 2‐propanethiolate moieties were oriented in axial‐equatorial ( anti ) manner while for complexes 1 and 2 , these were present in equatorial‐equatorial ( syn‐endo ) conformation [49] .…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Diiron bond length for the phosphine substituted complexes 1 (2.524 Å) and 2 (2.516 Å) were slightly longer than the all‐carbonyl complex A (2.510 Å); and the values were close to the Fe−Fe bond length found in the [2Fe‐2S] unit of the iron H 2 ase enzyme (2.6 Å) [44] . The Fe−P bond distances in 1 and 2 were 2.308 Å and 2.269 Å, respectively [45–48] . For complex A , the 2‐propanethiolate moieties were oriented in axial‐equatorial ( anti ) manner while for complexes 1 and 2 , these were present in equatorial‐equatorial ( syn‐endo ) conformation [49] .…”
Section: Resultsmentioning
confidence: 54%
“…[44] The FeÀ P bond distances in 1 and 2 were 2.308 Å and 2.269 Å, respectively. [45][46][47][48] For complex A, the 2-propanethiolate moieties were oriented in axial-equatorial (anti) manner while for complexes 1 and 2, these were present in equatorial-equatorial (syn-endo) conformation. [49] In both complexes 1 and 2, the phosphine group was bound to the diiron core in the apical position.…”
Section: Synthesismentioning
confidence: 99%
“…The limited examples reported include mostly hexacarbonyl and very few phosphine substituted mono‐ or diiron complexes [51–71] . Our group has also reported the redox and electrocatalytic properties of bis(monothiolato)‐based {FeFe} systems [72–77] wherein we have shown that the efficiency and stability of the catalysts vary with the type of monothiolate ligand used.…”
Section: Introductionmentioning
confidence: 91%
“…The complexes showed absorption bands due to π-π* transitions at lower wavelengths in the UV-region. The absorption bands of 2 (band 2) and 3 were found to be red-shifted compared to 1 indicating greater electron density at the diiron core due to attachment of electron-donating ligands [74,101] (Table S3, ESI).…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%
“…The chemical simulation of hydrogenase activity center has become a hot topic in the field of bioorganic chemistry. [11][12][13][14] Recently, Hogarth, Holt and coworkers [15] designed a complex Fe 2 (CO) 4 (m-DPPF)(m-pdt), which catalyzed both the oxidation of dihydrogen and conversion of protons into hydrogen. Inspired by that work, we synthesized an analogous complex [(m-(SCH(CH 2 CH 3 )CH 2 S))Fe(CO) 5 ] 2 (m,k 1 ,k 1 -DPPF) (DPPF = 1,1'-bis(diphenylphosphino)ferrocene) (complex 2) in order to investigate whether this complex could have the ability to catalyze both the proton reduction and phenol hydroxylation.…”
Section: Introductionmentioning
confidence: 99%